'We can't change much unless the exams change': Teachers' dilemmas in the curriculum reform in China. (March 2015) - Yan, Chunmei
This article reports on a study of English secondary teachers' perceptions of and implementation of the New English Curriculum Reform in China. Triangulated data collection methods were employed to gather information about teachers' perceptions of the New Curriculum and their teaching behaviours in Central China. An implementation gap emerged between the new curriculum requirements and the teachers' classroom practices, despite the teachers' common endorsement of the new curriculum goals and pedagogies due to a series of interrelated contextual constraints: the considerable professional and psychological challenges to teachers, the students' resistance, the lack of school support, physical constraints and, most importantly, the backwash effect of the prevalent examination culture in the Chinese society. The study suggests that it is crucially important to transform the current Gaokao-based assessments of schools and teachers to achieve alignment between the vision of educational policies on the curriculum reform and the reality of teachers' practices at the grassroots level.